RELIGION IN THOUGHT MURTADHA MUTHAHHARI - didin komarudin komarudin (Tsaqofah, 2020)
This writing is based on the background that religious formalism is increasingly becoming a fundamental problem. This is marked by the patterns and behavior of people who claim to be religious but there is no concrete implementation in their daily lives. This research was conducted to determine the concept of religion as a fitrah for humans as well as how religious beliefs are to the level of the relationship between religion and science according to Murtadha Motahhari. This research is a qualitative study that uses a sociological analysis approach, while the data in this study come from content analysis collected from various sources. , the level of religious belief, until people know God, the criticisms of Murtadha muthahhari which are an integral part of the life of the above figures to practice true religious values. Religion as human nature gives birth to the belief that religion is the only way to fulfill all needs, so that religion is not only a label or social formality but is able to become a guide in life and life. All religions teach goodness and peace, and no religion teaches violence. But sometimes there is violence in the name of religion because of a lack of understanding or a distortion of the source of religion itself. So that religion is sometimes used, and it seems that religion and religious practice are the opposite. So what is blamed on the concept of religion itself is actually the one who is wrong for religious actors.